Main Areas of the Implementation of Multiculturalism in Professional Educator Training in the USA - BAKHOV, Ivan Stepanovich (Journal of Research in Educational Sciences; Vol 8 No 10 (2017): Volume VIII, Issue 10, 2017, 2018)
The article raises the problem of professional preparation of future educators in the United States and Canada to work in a multicultural educational environment. Works of American and Canadian scholars dealing with issues of ethnocultural diversity of the educational environment of modern educational institutions and attempts to resolve them from the standpoint of a tolerant attitude in working with multiethnic and multicultural students are analyzed. Analysis of conceptual and empirical studies of American and Canadian authors, which until now have not been highlighted in the domestic press, is carried out. It is shown that teacher training programs at US colleges and universities, the curriculums and the policies of educational institutions have been revised to focus on the diversity of the ethnic composition of students and teachers, and that they reflect the main requirements of the goals and objectives of multicultural education.